2005
DOI: 10.1097/01.phm.0000176548.18362.67
|View full text |Cite
|
Sign up to set email alerts
|

Occult Periarthrosis of the Shoulder

Abstract: Nineteen outpatients, nine women and ten men, all right-handed, ranging in age from 33 to 87 yrs, with an average age of 53.5 yrs, presented with complaints of lateral epicondylitis (i.e., tennis elbow). Each was subsequently identified as having a heretofore unrecognized loss of ipsilateral shoulder internal rotation. The authors suggest that in this scenario the occult shoulder periarthrosis is interlinked in a pathokinetic chain potentially predisposing to the presenting symptoms of tennis elbow. During a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Lateral epicondylitis has been reported as a factor significantly associated with rotator cuff tear, 41 which supports our study results. Laban et al 22 reported that patients with lateral epicondylitis had previously unrecognized internal rotation deficit in their shoulders, a common finding in chronic rotator cuff tear. 40 Based on their finding, those authors postulated the biomechanical explanation that an internal rotation deficit could encourage eccentric movements of the hand and forearm, resulting in lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral epicondylitis has been reported as a factor significantly associated with rotator cuff tear, 41 which supports our study results. Laban et al 22 reported that patients with lateral epicondylitis had previously unrecognized internal rotation deficit in their shoulders, a common finding in chronic rotator cuff tear. 40 Based on their finding, those authors postulated the biomechanical explanation that an internal rotation deficit could encourage eccentric movements of the hand and forearm, resulting in lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%